Symposium 1: Tales from the Lands of Digital Natives - A Journey to Neverland - Ryberg, Thomas; Larsen, Malene Charlotte Ryberg (Proceedings of the International Conference on Networked Learning, 2012)
Within educational research it is becoming relatively well-established that the notions of digital natives or the net generation are problematic. We need to move beyond these broad generational terms to gain a deeper understanding of the students coming to Higher Education. This is important if we want to make considered and grounded choices in relation to developing networked learning. Rather than basing our expectations and designs in flawed assumptions about students' digital readiness or broad concepts about generational traits, we need to develop a more nuanced understanding of students' attitudes and ideas about technology. In this paper we provide a first reading and analysis of 130 blog posts produced by first semester students. We discuss central themes emerging from our reading, such as ambivalence and diversity in the students' feelings and attitudes towards networked technologies. We ask what characterises these young university students, and conclude by discussing the wider implications for networked learning.